Comparison of biomechanical properties in ascending aortic aneurysms of patients with congenital bicuspid aortic valve and Marfan syndrome. (1st March 2019) - ,; Loeys, Bart L.; Dietz, Harry C.; Van Laer, Lut; McCallion, Andrew S.; Eriksson, Per; Franco-Cereceda, Anders; Mertens, Luc; Mital, Seema; Mohamed, Salah A.; Andelfinger, Gregor; Yan, Junfeng; et al.
Abstract: Background: In patients with ascending aortic aneurysms (AscAA), biomechanical differences are seen among patients with congenital bicuspid aortic valves (BAV), Marfan syndrome (MFS), and tricuspid aortic valves (TAV). We examined the hemodynamic profiles and ultrastructures of aneurysmal specimens, focusing on vascular remodelling to better understand AscAA pathogenesis. Methods: A total of 795 patients with BAV (43.97 ± 0.51 years; 93.2% male), 69 with MFS (34.43 ± 1.44 years; 86.2% male), and 90 with TAV (67.27 ± 0.58 years; 60% male) were enrolled, primarily upon admission with AscAA. The biomechanical properties of the aortic root were assessed and intraoperative specimens were analyzed by light-microscopy and two-photon autofluorescence microscopy. Results: Patients with BAV had significantly greater distension of the aortic root, irrespective of age or aneurysmal widening ( R 2  = 0.543, p  < 0.05). This was associated with significantly increase in the size of the tunica media. Patients with MFS displayed significant stiffness in the sinuses that worsened with age ( R 2  = 0.752, p  < 0.001), similar to patients with TAV ( R 2  = 0.626, p  < 0.05). Patients with MFS showed significant root elasticity with aneurysmal growth ( R 2  = 0.596, p  < 0.05) and increased medial degeneration. Patients with TAV maintained biomechanical properties, apart from aneurysmal dimensions and high levels of inflammation. Conclusions: Among patients with AscAA, those with BAV maintain tissue elasticity in the aortic root, regardless of age. Patients with MFS demonstrate increased sinus stiffness with medial degeneration, both during aging and with aneurysmal growth. Patients with TAV and AscAA present with increased inflammation.